Problems of using terms in the state language in civil legislation (according to the text of the Civil Code of the Republic of Kazakhstan (Special part)) - Ilyassova, G.A.; Tokatov, R.A. (Bulletin of the Karaganda University “Law Series”, 2022)
The article summarizes the results of the linguistic examination of the texts of the Civil Code of the Republic of Kazakhstan (Special part) in the State and Russian languages. The purpose of the study is to identify inconsistencies in the translation of legal terms and provide the correct translation of terminology by conducting a comparative linguistic and legal examination of texts in two languages of the Civil Code of the Republic of Kazakhstan (Special part) to ensure the authenticity of texts of normative legal acts in Kazakh and Russian under part 3 of Article 24 of the Law of the Republic of Kazakhstan “On legal acts”. The results of the examination allow the authors to compile a “Unified dictionary of legal terms in the Kazakh language”. As most of the legal terms were introduced from English, French, Latin languages, they are used all over the world without changes. In this regard, the authors express their opinion about the use of legal terms of foreign origin in national legislation without translation into Kazakh. In the case of translation of terms of international law, its meaning does not coincide with the exact one, on the other hand, it is suggested that by using various similar words, we lose the quality of the law. In conclusion, the authors recommend that in order to ensure the correct translation of legal terms in civil legislation, it is necessary to unify and standardize them.